1992
DOI: 10.5006/1.3315963
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ferrous Sulfide Film from Sulfite on Steel Under Anaerobic Conditions

Abstract: The reactions of carbon steel and sulfite ions were studied by electrochemical experiments in 0.5 M NaCl solution under anaerobic conditions. Sulfite was reduced to sulfide, and a black ferrous sulfide film was formed. The process was monitored as a function of time at different potentials. During film formation, the current density and the intensity of reflected light from the steel surface were recorded. The film formation followed initially a 2-dimensional model and later a 3-dimensional model. The rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Chemical methods, such as addition of oxygen scavengers (sulfites and metasulfites), are mainly used as a backup for the physical process in case of malfunction or in order to remove the last traces of oxygen. Installation of vacuum towers or gas purging facilities has a high capital cost and a large footprint, while the use of sulfite based oxygen scavengers may have a negative impact on the environment and, if overdozed, also gives a high risk of sulfide corrosion of the piplines …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical methods, such as addition of oxygen scavengers (sulfites and metasulfites), are mainly used as a backup for the physical process in case of malfunction or in order to remove the last traces of oxygen. Installation of vacuum towers or gas purging facilities has a high capital cost and a large footprint, while the use of sulfite based oxygen scavengers may have a negative impact on the environment and, if overdozed, also gives a high risk of sulfide corrosion of the piplines …”
Section: Introductionmentioning
confidence: 99%
“…Installation of vacuum towers or gas purging facilities has a high capital cost and a large footprint, while the use of sulfite based oxygen scavengers may have a negative impact on the environment and, if overdozed, also gives a high risk of sulfide corrosion of the piplines. 2 The use of an electrochemical process for the removal of oxygen from seawater is an alternative method that avoids the disadvantages described for the other methods. 3−5 The oxidation of water to yield hydroxium ion and oxygen, and the reduction of oxygen to water are the basis for deoxygenation of water.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen removal to a concentration less than 10 ppb can be achieved with the use of oxygen scavengers . However, many of the chemicals for oxygen removal are not environmentally friendly, and some chemicals can have a severe negative impact on the occupational safety of the personnel involved in the process, and may in addition increase corrosion when used in too high doses . The scavenging ability of these chemicals depends on pH and temperature, and catalysts might be required in order to have a sufficient reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ruhl and Kranzmann [38] suggested that the inner part of the FeSO 3 · x H 2 O and FeSO 4 · x H 2 O layers changed to iron sulphide (FeS) under ambient pressure. The changing process was characterised by the following equation [123]: When NO x and SO x were present, ammoniojarosite ((NH 4 )Fe 3 (SO 4 ) 2 (OH) 6 ) was found to be the main corrosion product under ambient conditions [36], while Fe(NO 3 ) 3 .9H 2 O and Fe 2 O 3 .H 2 O were detected as the main corrosion products for X65 steel in water-saturated supercritical CO 2 with 1000 ppmv NO 2 [91]. NO 3 – present in the solution might be reduced to ammonium (NH 4 + ) within the aqueous film and in the presence of hydronium ions (H 3 O + ) [37], according to the following equation [124]: …”
Section: Influential Parameters and Mechanismsmentioning
confidence: 99%